Wastewater reuse and recycling systems: a perspective into India and Australia - Mekala, Gayathri Devi; Davidson, B.; Samad, Madar; Boland, A.M. (International Water Management Institute, 2008)
With issues of climate change, increase in urban population and the increased demand for water from competing sectors, wastewater recycling is becoming an important strategy to complement the existing water resources for both developing and developed countries. There are lessons, experiences, data and technology that can be shared for mutual benefit. The current paper is part of a doctoral research and presents a comprehensive literature review on the following issues in India and Australia: some key statistics of wastewater use and recycling; rationale for wastewater use; problems in promoting recycling; research gaps; economic characteristics of wastewater; wastewater markets and its future potential.